2007
DOI: 10.1098/rspb.2007.0088
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome painting among Proboscidea, Hyracoidea and Sirenia: support for Paenungulata (Afrotheria, Mammalia) but not Tethytheria

Abstract: Despite marked improvements in the interpretation of systematic relationships within Eutheria, particular nodes, including Paenungulata (Hyracoidea, Sirenia and Proboscidea), remain ambiguous. The combination of a rapid radiation, a deep divergence and an extensive morphological diversification has resulted in a limited phylogenetic signal confounding resolution within this clade both at the morphological and nucleotide levels. Cross-species chromosome painting was used to delineate regions of homology between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 46 publications
3
38
0
1
Order By: Relevance
“…60 mys) and a rapid paenungulate radiation at the CretaceousTertiary (KT) transition, which is also supported by the latest genomic studies (26)(27)(28). Rapid paenungulate radiation and fossil gaps may explain poorly resolved interordinal relationships.…”
Section: Discussion and Implications For The Placental Radiationmentioning
confidence: 61%
“…60 mys) and a rapid paenungulate radiation at the CretaceousTertiary (KT) transition, which is also supported by the latest genomic studies (26)(27)(28). Rapid paenungulate radiation and fossil gaps may explain poorly resolved interordinal relationships.…”
Section: Discussion and Implications For The Placental Radiationmentioning
confidence: 61%
“…In contrast, 12 chromosomal changes detected in M. thomasi and between 6 and 13 (depending on which matrix is considered) in M. cowani punctuate the õ9.9 Myr that separate these two species from the Microgale ancestor ( Figure 5), mimicking the karyotypic megaevolution of certain bat species (Baker & Bickham 1980). Although these rates are lower than those observed in several mammals (e.g., Britton-Davidian et al 2000, Wang & Lan 2000, Dobigny et al 2005, they are clearly accelerated with respect to most Afrotheria, the only exception being within the Sirenia where at least four chromosomal changes separate Trichechus inunguis and T. manatus, taxa that are thought to have diverged 1Y4 Myr ago (Pardini et al 2007). Chromosomal mutation rates depend on many factors including population dynamics, life history and genomic traits of the species concerned.…”
Section: Rates Of Chromosomal Evolution Within the Oryzorictinaementioning
confidence: 89%
“…Previous studies have shown that Afrotheria with disparate morphological characters are united by shared derived syntenic associations such as HSA 3/21/5 and 1/19p [Frönicke et al, 2003;Yang et al, 2003;Robinson et al, 2004;Kellogg et al, 2007;Pardini et al, 2007]. Interestingly, based on the combined analysis of comparative chromosome maps among the 2-toed sloth ( C. didactylus , CDI), tree anteater ( T. tetradactyla , TTE) and human, Yang et al [2006] proposed that 2 derived segmental associations (HSA 2/8 and 7a/10p) existing in the genomes of C. didactylus and T. tetradactyla could be regarded as the cytogenetic signatures for Xenarthra.…”
Section: Cytogenetic Signatures For the Xenarthramentioning
confidence: 99%